Winstedt Dan Pendidikan Orang Melayu - Ismail, Abdul Hadi (Penerbit Universiti Sains Malaysia, 1994)
Winstedt's contribution to the development of the Malay language and literature is well-known to students of language and literary history in this country. However, the part he played in the retardation of Malay education whilst he was the Assistant Director of Education in the Straits Settlements and the colonial officer in charge of native education in the Federated Malay Status - is an instance in the history of education of this country that is not often realised by most people. As far as Winstedt is concerned, this is a paradox, most incongruous for one associated with a "love for the Malays and their language, and ... enthusiasm for their progress" (Bastin and Roolvink, 1967: 6). This article attemps to examine this lesser known, but highly significant role of Winstedt as the architect of Malay education.